Analysis of Rain Water Acidity in Padang City - Nova, Sari; Mariya, Sri; Rahmi, Lailatur; Putri, Srikandi; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The fast growth of population, the increased flow of transportation, industry spread in Padang Municipality, and thermal inverse effect can trigger air pollution leading to acid rain in the municipality. The aims of this study are to analyze the nitrate, sulfur and pH contents of rain water and to analyze the effect of rain intensity, air temperature, air pressure, and wind direction and speed on the acidity of rain water in Padang Municipality. The study was conducted using a field measurement and a laboratory test. The sample of rain water was collected by a purposive sampling technique as displayed in Thiessen polygon. The sample of rain water was collected in ten times of sampling in six regions of Thiessen polygon in Padang Municipality. The data collected were analyzed by climate data analysis, rain intensity analysis, multiple linier regression analysis, spatial analysis, and descriptive analysis. The results of the laboratory test showed that sulphate and nitrate contents in rain water in Padang Municipality was still under the threshold of clean water quality No. 416/MENKES/PER/IX/1990, i.e. 400 mg/l for sulphate and 10 mg/l for nitrate. The effect of rain intensity on the acidity of rain water was inversely proportional to sulphate and nitrate contents and directly proportional to pH. The results of validation test and multiple linear regression analysis about the effect of sulphate, nitrate, and pH contents and independent variable as the selected factor displayed in classic assumption test showed that sulphate and pH contents had a significant effect, while nitrate content had no significant effect